The Association Between the Mediterranean Diet and Fatty Acids in Red Blood Cells of Spanish Adolescents - Ayala-Aldana, Nicolas; Lafuente, David; Lázaro, Iolanda; Pinar-Martí, Ariadna; Manidis, Alexios; Bernardo-Castro, Sara; Fernandez-Barres, Silvia; Healy, Darren R.; Vrijheid, Martine; Contreras-Rodríguez, Oren; Sala-Vila, Aleix; Julvez, Jordi (Nutrients, 2025)
Objective: The Mediterranean diet (MedDiet) is characterized by its emphasis on plant-based foods, olive oil, and fish products, and has been associated with providing relevant fatty acids (FAs) for adolescent physiology. This study aims to investigate the relationship between adherence to the MedDiet and the FA composition of red blood cell (RBC) membranes in an adolescent population. Methods: The current research examines the relationship between MedDiet adherence, assessed using the KIDMED questionnaire, and the composition of RBC membranes, specifically measuring 22 FAs in a cross-sectional analysis of adolescents from two cohorts (mean age = 14.55). Baseline data from 552 participants with complete dietary adherence and FA information were analyzed using multivariable regression models and principal component analysis (PCA) as confirmatory analysis. All regression models were adjusted by age, sex, body mass index, physical activity, maternal education and cohort enrollment. Results: Main results shown that “Good adherence” to the MedDiet was positively associated with omega-3 FAs, including eicosapentaenoic acid (β = 0.34; 95% CI: 0.17, 0.52; p-value < 0.001) and docosahexaenoic acid (β = 0.29; 95% CI: 0.11, 0.46; p-value = 0.001), and inversely associated with specific omega-6 FAs, such as arachidonic acid (β = −0.28; 95% CI: −0.46, −0.11; p-value = 0.002) and adrenic acid (β = −0.19; 95% CI: −0.30, −0.08; p-value < 0.001). PCA identified distinct FA patterns, with “Good adherence” to the MedDiet being associated with an increase in the omega-3 FAs pattern (β = 0.32; 95% CI: 0.14, 0.49; p-value < 0.001). These findings remained robust after multiple test comparisons. Conclusions: This study underscores the potential of the MedDiet to promote optimal RBC FA composition in healthy adolescents, characterized by high levels of omega-3 FAs and reduced levels of arachidonic acid and adrenic acid in RBC membranes.